2016
DOI: 10.3348/kjr.2016.17.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Evaluation of Bony Nasolacrimal Canal in a Caucasian Population with Primary Acquired Nasolacrimal Duct Obstruction: A Multidetector Computed Tomography Study

Abstract: ObjectiveThe bony nasolacrimal duct (BNLD) morphology as a contributory factor in primary acquired nasolacrimal duct obstruction (PANDO) is still controversial. The objectives of this study were to evaluate the morphometric differences of BNLDs in unilateral PANDO patients between PANDO and non-PANDO sides, as compared with the control group using multidetector computed tomography (CT).Materials and MethodsBilateral BNLDs in 39 unilateral PANDO patients and 36 control subjects were retrospectively reviewed. CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 15 publications
2
21
3
2
Order By: Relevance
“…The entrance diameter does not differ among populations except in the study by Takahashi et al (2013b), in which the smallest diameter differed among populations. More specifically, Bulbul et al (2016) and Ramey et al (2013) found that the smallest transverse diameter tended to be smaller in specimens of Western than in East Asians populations (Takahashi et al, 2013b). This difference may explain why Caucasians have a higher incidence of acquired NLD obstruction than other populations (Janssen et al, 2001; Post, 1969; Takahashi et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The entrance diameter does not differ among populations except in the study by Takahashi et al (2013b), in which the smallest diameter differed among populations. More specifically, Bulbul et al (2016) and Ramey et al (2013) found that the smallest transverse diameter tended to be smaller in specimens of Western than in East Asians populations (Takahashi et al, 2013b). This difference may explain why Caucasians have a higher incidence of acquired NLD obstruction than other populations (Janssen et al, 2001; Post, 1969; Takahashi et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…This difference may explain why Caucasians have a higher incidence of acquired NLD obstruction than other populations (Janssen et al, 2001; Post, 1969; Takahashi et al, 2013b). Meanwhile, length variables tend to be longer in Caucasian and Black specimens than in East Asians (Bulbul et al, 2016; Ramey et al, 2013). This difference may be influenced by differences in the structure of the nose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para avaliação das estruturas da cavidade nasal e dos seios paranasais, a fim de identificar as possíveis causas da obstrução do ducto nasolacrimal, segundo Bolzan e Tucunduva 9 (2012), é indicado o uso de tomografia computadorizada (TC), pois possibilita análise detalhada devido à redução na sobreposição de imagens, relacionadas as radiografias. Em concordância com a escolha de método, Bulbul et al 10 em 2016 avaliaram a diferença morfológica da obstrução do ducto lacrimonasal por TC.…”
Section: Introductionunclassified
“…인 역시 관련성이 있음을 보여준다 4. 8 Bulbul et al 4 과 Janssen et al 6 은 코눈물관막힘 환자에서 정상인보다 코눈물 관의 가로 직경이 좁다고 보고하였다.…”
unclassified